2021
DOI: 10.1016/j.jtocrr.2021.100205
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes With Pembrolizumab Monotherapy in Patients With Programmed Death-Ligand 1–Positive NSCLC With Brain Metastases: Pooled Analysis of KEYNOTE-001, 010, 024, and 042

Abstract: Introduction: We retrospectively evaluated outcomes in patients with programmed death-ligand 1 (PD-L1)-positive NSCLC to determine whether baseline (i.e., at study enrollment) brain metastases were associated with the efficacy of pembrolizumab versus chemotherapy.Methods: We pooled the data for patients with previously treated or untreated PD-L1-positive (tumor proportion score [TPS], !1%) advanced metastatic NSCLC in KEYNOTE-001 (NCT01295827), KEYNOTE-010 (NCT01905657), KEYNOTE-024 (NCT02142738), and KEYNOTE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 27 publications
(50 reference statements)
4
36
0
Order By: Relevance
“…( 32 ) reported that no intracranial Grade≥3 adverse events (AEs) occurred, and the incidence of systemic Grade≥3 AEs was 14%. In the pooled analysis of KEYNOTE-001, 010, 024, and 042 ( 44 ), comparing pembrolizumab and chemotherapy, the incidence of intracranial Grade≥3 AEs was 9.7% vs. 26.7%, while the incidence of systemic Grade≥3 AEs was 14.8% vs. 45.6%. The Expanded Access Program from Italy included 466 NSCLC patients with BMs who were asymptomatic after radiotherapy.…”
Section: Ici Monotherapy For Nsclc-bmsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 32 ) reported that no intracranial Grade≥3 adverse events (AEs) occurred, and the incidence of systemic Grade≥3 AEs was 14%. In the pooled analysis of KEYNOTE-001, 010, 024, and 042 ( 44 ), comparing pembrolizumab and chemotherapy, the incidence of intracranial Grade≥3 AEs was 9.7% vs. 26.7%, while the incidence of systemic Grade≥3 AEs was 14.8% vs. 45.6%. The Expanded Access Program from Italy included 466 NSCLC patients with BMs who were asymptomatic after radiotherapy.…”
Section: Ici Monotherapy For Nsclc-bmsmentioning
confidence: 99%
“…Compared with chemotherapy, a higher systemic response has been observed in ICI monotherapy for patients with BMs. Recently, a pooled analysis based on KEYNOTE-001, 010, 024, and 042 ( 44 ) showed that systemic ORR with pembrolizumab was superior to chemotherapy in PD-L1≥1% NSCLC patients with BMs (26.1% vs. 18.1%). The single-arm FIR trial ( 45 ) enrolled 13 advanced NSCLC patients treated with atezolizumab into its cohort 3 (second-line with treated BMs).…”
Section: Ici Monotherapy For Nsclc-bmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pooled analysis from Keynote 001, Keynote 010, Keynote 024, and Keynote 42 trials, Mansfield et al evaluated the efficacy and safety of pembrolizumab monotherapy versus chemotherapy in metastatic NSCLC patients with BM at baseline ( 14 ). Only patients with PD-L1 ≥1% were included in this post-hoc analysis.…”
Section: Immune Checkpoint Inhibitors Are Safe In Nsclc Patients With...mentioning
confidence: 99%
“…In the pooled analysis from Keynote 001, Keynote 010, Keynote 024, and Keynote 42 trials, the patients had received pembrolizumab or standard chemotherapy in different settings, including as first-line treatment ( 14 ). After a median follow-up of 12.9 months, pembrolizumab provided a longer overall survival compared to chemotherapy regardless of the presence of BM at baseline (HR 0.83 and HR 0.78 in patients with and without BM, respectively) ( Figure 2 ).…”
Section: Immune Checkpoint Inhibitors Are Effective In Nsclc Patients...mentioning
confidence: 99%